2004
DOI: 10.1152/ajpheart.00247.2004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of fatty acid-induced apoptosis by low-dose alcohol in neonatal rat cardiomyocytes

Abstract: . Attenuation of fatty acid-induced apoptosis by lowdose alcohol in neonatal rat cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
2
10
0
Order By: Relevance
“…This observation is consistent with previous studies, which suggest that a high concentration of palmitic acid decreases mitochondrial membrane potential, and the ability of the mitochondria to produce ROS [34,35]. Provision of a low concentration of metformin (1 or 2 mmol/l) restored ROS to control levels, probably due to the effect of metformin in promoting fatty acid oxidation and electron flow through the mitochondrial electron transport chain [35]. In contrast, in the presence of palmitic acid, cardiomyocytes treated with 5 mmol/l metformin exhibited the lowest ROS level.…”
Section: Discussionsupporting
confidence: 93%
“…This observation is consistent with previous studies, which suggest that a high concentration of palmitic acid decreases mitochondrial membrane potential, and the ability of the mitochondria to produce ROS [34,35]. Provision of a low concentration of metformin (1 or 2 mmol/l) restored ROS to control levels, probably due to the effect of metformin in promoting fatty acid oxidation and electron flow through the mitochondrial electron transport chain [35]. In contrast, in the presence of palmitic acid, cardiomyocytes treated with 5 mmol/l metformin exhibited the lowest ROS level.…”
Section: Discussionsupporting
confidence: 93%
“…Saturated fatty acids such as palmitic acid stimulated AMPK activity in the presence of ethanol in cardiomyocytes. 36 We also observed that PGC-1␣ promoter activity in vitro is modified by various fatty acids only in the presence of ethanol (unpublished data). These direct effects could be, in part, due to the differences in the metabolism of PUFA and HSF in the presence or absence of ethanol.…”
Section: Discussionmentioning
confidence: 62%
“…Second, it is possible that a counteractive effect may exist between ethanol and a high-fat diet. For example, ethanol attenuates fatty acid-induced apoptosis in neonatal rat cardiomyocytes [54] . Diets rich in saturated fatty acids protect against alcoholic liver injury [55][56][57][58][59][60] .…”
Section: Wwwchinapharcom Feng L Et Almentioning
confidence: 99%